Mechanisms of the Masquelet technique to promote bone defect repair and its influencing factors - Jiang-Hong Wu; Quan-Wei Bao; Shao-Kang Wang; Pan-Yu Zhou; Shuo-Gui Xu (Chinese Journal of Traumatology)
The Masquelet technique, also known as the induced membrane technique, is a surgical technique for repairing large bone defects based on the use of a membrane generated by a foreign body reaction for bone grafting. This technique is not only simple to perform, with few complications and quick recovery, but also has excellent clinical results. To better understand the mechanisms by which this technique promotes bone defect repair and the factors that require special attention in practice, we examined and summarized the relevant research advances in this technique by searching, reading, and analysing the literature. Literature show that the Masquelet technique may promote the repair of bone defects through the physical septum and molecular barrier, vascular network, enrichment of mesenchymal stem cells, and high expression of bone-related growth factors, and the repair process is affected by the properties of spacers, the timing of bone graft, mechanical environment, intramembrane filling materials, artificial membrane, and pharmaceutical/biological agents/physical stimulation.